Effective female flower variation estimate of guarana tree paullinia cupana var. Sorbilis - Escobar, José Ricardo (Pesquisa Agropecuaria Brasileira, 2014)
An indirect method, to estimate the period, variation and amount of effective female flower of the guarana tree, is described. The method is based on individual seed production by date of harvest, one seed weight and fruit ripening period. Using data of 412 trees, the estimated number of effetive flower was 1.200 per plant under local conditions and for 1982 harvest. The flowering started in the beginning of July and finished during the first week of October. The peak of effective flowers, occurred during the first two weeks of September.